EFEKTIVITAS PEMBELAJARAN MELAKSANAKAN PEKERJAAN SURVEI DASAR MELALUI MODEL PEMBELAJARAN INKUIRI PADA SISWA KELAS X TGB SMK NEGERI 5 SURAKARTA - Kurniawan, Nova; Thamrin, A G; Agustin, Rima Sri (Pendidikan Teknik Bangunan, 2013)
ABSTRACTNova Kurniawan. THE EFFECTIVENESS OF WORKING BASIC SURVEY BY INQUIRY LEARNING MODEL IN THE STUDENTS OF 10TH GRADE TGB SMK NEGERI 5 SURAKARTA BASIC SURVEY. Thesis, Faculty of Learning and Education Universitas Sebelas Maret Surakarta. July 2013. Based on data and teaching experience in SMK Negeri 5 Surakarta for 3 months, most of 10th grade TGB students find the difficulty on finished the MPSD subject exercises. It caused by the students less comprehends about the materials. In this research, the researcher tries to use inquiry teaching method as the one of alternative to solve the problem. The purposes of this study are to make the students more active in lesson activity in the class, to make the students more capable and brave to delivers their idea or opinion, and to increase the result of MPSD subject. This research takes place at 10th grade of TGB class in SMK N 5 Surakarta. The students of 10th grade of TGB are 21. Most of them are passive students in lesson activity. Besides, many students find the difficulty to comprehend the material about Working Basic Survey (MPSD). The research focuses on low bravery student to asking to the teacher and the using of imprecise method and learning model. The first step is the researcher begins to make lesson plan in the inquiry model, make observation paper, and design the evaluation instrument. Then, at the lesson activity, the researcher or collaborator observe and take a note all of the activity based on the instrument that planned before. At the learning class research, there are two actions. The percentage of first action is 66,70%. The percentage of second activity is 85,71%. The next step is observation. In observation, the research collected, analyzed and reflected the data. The conclusions of this research are by using inquiry model, the result of learning student is increase, the students more active, and the students more capable and brave to delivers their idea or opinion in lesson activity.